Techno-Economic Study of Biodiesel Generation from Sterculia foetida Seeds - Bilqist Imeilia Az Zahra; H.C. Theofany; Teuku Meurah Indra Riayatsyah; H.B. Aditiya; Bidattul S Zainal (Politeknik Negeri Medan, 2025)
As fossil fuel reserves diminish and energy demand grows, biodiesel from non-edible oils has emerged as a promising renewable alternative. This study evaluates the feasibility of producing biodiesel from Sterculia foetida (Java olive) seeds, which contain 50–60 % oil. A second-generation biodiesel plant is designed and simulated using SuperPro Designer, covering oil extraction, transesterification, product purification, and by-product recovery. The plant processes 4,396 kg of seeds per hour in Lombok (Indonesia). Material and energy balances indicate nearly complete conversion to biodiesel, yielding 16.19 million kg/year with a 0.001 % mass balance error. The total utility power demand is 6.2 million kWh/year, with the transesterification reactor consuming 27 %. Economic evaluation (2021 USD) shows a capital investment of 3.82 million and annual operating cost of 20.72 million. At a biodiesel price of 1.00/L, annual revenue is 21.47 million, including 2.4 million from glycerol and co-products. Profitability metrics are positive: gross margin 3.48 %, ROI 19.67 %, payback period 5.08 years, IRR 9.14 %, and NPV 1.03 million. Sensitivity analysis shows profitability is most affected by biodiesel market price and feedstock cost. Overall, biodiesel production from Sterculia foetida is technically feasible and economically viable, diversifying Indonesia’s biodiesel feedstocks.